2021
DOI: 10.1002/pros.24104
|View full text |Cite
|
Sign up to set email alerts
|

Imaging expression of prostate‐specific membrane antigen and response to PSMA‐targeted β‐emitting radionuclide therapies in metastatic castration‐resistant prostate cancer

Abstract: Background Prostate‐specific membrane antigen (PSMA)‐targeted radionuclide therapy (TRT) has demonstrated efficacy and tolerability with a dose–response effect in phase I/II trials in men with metastatic castration‐resistant prostate cancer (mCRPC). The need for positive PSMA imaging before PSMA‐TRT to select patients is largely practiced, but its utility is not proven. Given target heterogeneity, developing a biomarker to identify the optimal patient population remains an unmet need. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Each patient must undergo PSMA imaging, for example 68 Gallium (Ga)-PSMA-PET, to prove the presence and to quantify the amount of uptake of PSMA in tumour lesions. Whether the amount of PSMA-tracer uptake has an impact on the following RLT and its efficacy remains unclear to this point [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Eligibility and Procedures Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each patient must undergo PSMA imaging, for example 68 Gallium (Ga)-PSMA-PET, to prove the presence and to quantify the amount of uptake of PSMA in tumour lesions. Whether the amount of PSMA-tracer uptake has an impact on the following RLT and its efficacy remains unclear to this point [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Eligibility and Procedures Guidelinesmentioning
confidence: 99%
“…PSMA expression might predict and prognosticate response and outcome [ 19 , 20 , 22 , 23 ]. It seems logical that a higher PSMA expression is linked to a better response to PSMA targeted RLT.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…One group has used a five-point imaging score (IS) which was assigned based upon PSMA uptake in tumors compared to liver uptake and scored by two independent radiologists on a 0–4 scale [ 11 , 12 ]. PET images were scored by averaging SUV max of the five lesions with highest uptake and then comparing that value with liver SUV mean .…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Planar single photon imaging was also studied, scoring the three lesions with the highest uptake. Using this assessment in 215 men with progressive mCRPC who were treated with β-emitting radionuclides ( 177 Lu-J591, 177 Lu-PSMA-617, 90 Y-J591, 177 Lu-J591 + 177 Lu-PSMA-617), a high IS of 2–4 was independently associated with ≥50% decrease in PSA, after accounting for CALGB (Halabi) prognostic score, dose administered, and previous taxane use [ 11 ].…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Studies reported that the whole-body PSMA PET SUV mean correlated with outcomes of patients treated with 177 Lu-PSMA (7,11,12). In a study conducted at Weill Cornell, fewer than 10% of patients with no or low PSMA expression at baseline had a significant PSA response to PSMA-targeted MRT (13).…”
mentioning
confidence: 99%